Do public health interventions crowd out private health investments? Malaria control policies in Eritrea - Pedro Carneiro; Andrea Locatelli; Tewolde Ghebremeskel; Joseph Keating (Institute for the Study of Labor (IZA), 2012)
It is often argued that engaging in indoor residual spraying (IRS) in areas with high coverage of mosquito bed nets may discourage net ownership and use. This is just a case of a public program inducing perverse incentives. We analyze new data from a randomized control trial conducted in Eritrea which surprisingly shows the opposite: IRS encouraged net acquisition and use. Our evidence points to the role of imperfect information. The introduction of IRS may have made the problem of malaria more salient, leading to a change in beliefs about its importance and to an increase in private health investments.
urn:nbn:de:101:1-201301212776
Keywords: D12; D83; H42; I10; I12; 330; malaria; bed nets; indoor residual spray; information; beliefs; behavior; crowding out; health; developing countries; Tropenkrankheit; Gesundheitspolitik; Gesundheitsvorsorge; Verhalten; Eritrea